Generalized strong vector quasi-equilibrium problem with domination structure - Fu, Junyi; Wang, Sanhua (Journal of global optimization, 2013)
In this paper, a generalized strong vector quasi-equilibrium problem with set-valued mapping and domination structure is presented, and under the condition of cone-continuity, existence of solutions and the compactness of solution set are established. As applications, existence of solutions for strong vector F-implicit variational inequality problem and strong vector F-implicit complementarity problem is derived, and Khan’s main results are corrected.